Feasibility of cerebral blood flow and oxygenation monitoring by continuous transcranial Doppler combined with cerebral oximetry in a patient with refractory cardiac arrest treated by extracorporeal life support. (November 2014) - Belohlavek, J; Skalicka, H; Boucek, T; Kovarnik, T; Fichtl, J; Smid, O; Huptych, M; Linhart, A
The adequacy of cerebral blood flow and the level of regional oxygen saturation during CPR and early post-resuscitation phases assuring favorable neurological outcome are not known. We demonstrate the feasibility of cerebral blood flow and oxygenation monitoring by a continuous transcranial Doppler combined with cerebral oximetry in a patient with refractory cardiac arrest treated by extracorporeal life support.